Work experience was associated with the knowledge and practice of catheter-associated urinary tract infection prevention among nurses at University of Gondar Comprehensive Specialized Hospital, northwest Ethiopia, 2021 - Alebachew Ferede Zegeye; Chanyalew Worku Kassahun; Yemataw Zewdu Temachu (BMC, 2023)
Abstract Background Catheter-associated urinary tract infection is the source of about 20% of episodes of health-care acquired infections in acute care facilities and it is over 50% in long-term care facilities. In Ethiopia, there is no published scientific research regarding knowledge and practice of nurses on catheter-associated urinary tract infections prevention. Therefore, this study aimed to assess knowledge, practice and associated factors of CAUTI prevention among nurses working at university of Gondar comprehensive specialized hospital, northwest Ethiopia, 2021. Methods Institutional based cross sectional study was conducted at University of Gondar Comprehensive Specialized Referral Hospital from April 01 to May 01, 2021 among 423 nurses. Simple random sampling technique was used. Data were collected by using self-administered questionnaire then coded and entered into EPI- Data version 4.6 and then exported to SPSS version 23. Descriptive statistics was computed, and the result was summarized by texts, tables, and charts. All variables with P-value < 0.25 in the univariate analysis were included in the multivariable regression analysis. The degree of association was interpreted by using the adjusted odds ratio with 95% confidence intervals. Results Good knowledge and practice of nurses towards CAUTI prevention was 37.7% and 51.8% respectively. Good knowledge was associated with sex [AOR = 1.84, 95% CI (1.09, 3.11)], work experience [AOR = 2.36, 95% CI (1.09, 5.10)], working unit [AOR = 6.9, 95% CI (2.11, 22.52)], training [AOR = 2.33, 95% CI (1.17, 4.65)] and had guideline [AOR = 2.78, 95% CI (1.59, 4.88)]. Good practice was associated with sex, work experience, attitude and knowledge towards CAUTI prevention [AOR = 2.19, 95% CI (1.23, 3.88)], [AOR = 5.44, 95% CI (1.66, 17.84)], [AOR = 3.06, 95% CI (1.65, 5.67)], and [AOR = 5.28, 95% CI (2.86, 9.76)] respectively. Conclusions Nearly one-third of nurses had good knowledge and more than half of nurses had good practice towards CAUTI prevention. Sex, work experience, work unit, presence of guideline, and training were significantly associated with knowledge. Sex, work experience, good attitude and, knowledge were associated with practice of nurses towards CAUTI prevention. The knowledge and practice towards catheter associated urinary tract infection prevention among nurses should be increased, so that the patients could enjoy and maintain the healthy lifestyle.